A bioinformatic approach to identify confirmed and probable CRISPR–Cas systems in the Acinetobacter calcoaceticus–Acinetobacter baumannii complex genomes - Mancilla-Rojano, Jetsi; Flores, Víctor; Cevallos, Miguel A.; Ochoa, Sara A.; Parra-Flores, Julio; Arellano-Galindo, José; Xicohtencatl-Cortes, Juan; Cruz-Córdova, Ariadnna (Frontiers in Microbiology, 2024)
The Acinetobacter calcoaceticus–Acinetobacter baumannii complex, or Acb complex, consists of six species: Acinetobacter baumannii, Acinetobacter calcoaceticus, Acinetobacter nosocomialis, Acinetobacter pittii, Acinetobacter seifertii, and Acinetobacter lactucae. A. baumannii is the most clinically significant of these species and is frequently related to healthcare-associated infections (HAIs). Clustered regularly interspaced short palindromic repeat (CRISPR) arrays and associated genes (cas) constitute bacterial adaptive immune systems and function as variable genetic elements. This study aimed to conduct a genomic analysis of Acb complex genomes available in databases to describe and characterize CRISPR systems and cas genes. A total of 293 genomes representing six Acb species exhibited CRISPR-related sequences. These genomes originate from various sources, including clinical specimens, animals, medical devices, and environmental samples. Sequence typing identified 145 ribosomal multilocus sequence types (rSTs). CRISPR‒Cas systems were confirmed in 26.3% of the genomes, classified as subtypes I-Fa, I-Fb and I-Fv. Probable CRISPR arrays and cas genes associated with CRISPR‒Cas subtypes III-A, I-B, and III-B were also detected. These arrays often contained 2 to 6 repeat sequences. Some of the CRISPR‒Cas systems are associated with genomic regions related to Cap4 proteins, toxin–antitoxin systems, and other genetic elements. Moreover, prophage sequences were prevalent in 68.9% of the genomes. Analysis revealed a connection between these prophages and CRISPR‒Cas systems, indicating an ongoing arms race between the bacteria and their bacteriophages. Furthermore, proteins associated with anti-CRISPR systems, such as AcrF11 and AcrF7, were identified in the A. baumannii and A. pittii genomes. This study elucidates CRISPR‒Cas systems and defence mechanisms within the Acb complex, highlighting their diverse distribution and interactions with prophages and other genetic elements. This study also provides valuable insights into the evolution and adaptation of these microorganisms in various environments and clinical settings.